Preparation method of high-performance ferric sodium pyrophosphate positive electrode material

By doping high-valent transition metal elements into the positive electrode material of sodium ion battery and introducing iron defects, the problems of poor conductivity and low compaction density of the material are solved, and the electrochemical performance and practicality are significantly improved.

CN119812312APending Publication Date: 2025-04-11JIANGSU UNIV

Patent Information

Application Number
CN202510016732.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The positive electrode material of sodium ion battery, sodium phosphate, has problems such as poor conductivity, poor ionic conductivity, low compaction density, and prone to inactive impurities during preparation, which affects its electrochemical performance.

Method used

Through the design of doping high-priced transition metal elements (such as molybdenum and tungsten) with iron defects, the structure and electron cloud density of the material are regulated, the conductivity and compaction density of the material are improved, and the generation of heterophases is suppressed.

Benefits of technology

The electrochemical performance of the cathode material of sodium ion battery is significantly improved, including improving compaction density, electrochemical specific capacity and cycle life, while simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812312A_ABST
    Figure CN119812312A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion battery positive electrode materials, and discloses a preparation method of a high-performance ferric pyrophosphate sodium positive electrode material. Performing high-energy ball milling on a sodium source, an iron source, a phosphorus source, an A source and a carbon source to obtain a precursor; and then annealing the precursor in argon to obtain the ferric sodium pyrophosphate positive electrode material doped with high-valence transition metal elements and subjected to iron defect engineering. Through doping of high-valence transition metal elements and regulation and control of iron defect sites, the technical problems that the ferric sodium phosphate pyrophosphate type positive electrode material is poor in conductivity, poor in ionic conductivity and low in compaction density, inactive impurities are easily generated in the preparation process, and the electrochemical performance of the ferric sodium phosphate pyrophosphate type positive electrode material is affected are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically is a sodium ion battery positive electrode material doped with a high-valent transition metal element and iron defect engineering, a preparation method thereof, and an application thereof. Background Art

[0002] The development of renewable energy sources such as solar energy, wind energy, and tidal energy is of great significance to achieving sustainable development of human society. Considering the instability of these energy sources, the establishment of smart grids based on large-scale energy storage systems (LSESSs) is crucial to achieve efficient utilization of energy. In recent years, lithium resources have become increasingly scarce and will no longer be able to meet the needs of large-scale energy storage in the future. Therefore, it is necessary to develop new material systems that can partially replace lithium-ion batteries. Due to the advantages of sodium resources such as low cost, high abundance, and wide distribution, sodium-ion batteries are considered to be a very promising option in large-scale energy storage. However, although many efforts have been invested in the development of sodium-ion batteries, it is still a huge challenge to obtain high-performance and low-cost sodium-ion battery cathode materials.

[0003] As one of the most typical iron-based mixed phosphates, Na4Fe3(PO4)2(P2O7)(NFPP) has attracted wide attention as a cathode material for SIBs since it was first proposed by Kim et al. in 2012. Despite its high molecular weight, it can obtain a satisfactory theoretical specific capacity due to the presence of an iron ion redox pair. In addition, due to the polyanion group PO4 3- and P2O7 4- The average working voltage generated by the inductive effect is 3.1V (relative to Na + / Na), which is higher than most single polyanion systems. In addition, NFPP has a typical NASICON-type (sodium superionic conductor) structure, in which the three-dimensional (3D) crystal framework and stable ion diffusion channels provide strong support for the extraction / embedding of sodium ions. However, the NFPP system still has some difficult-to-overcome problems, such as poor conductivity and low compaction density, which seriously affect the application of sodium iron phosphate pyrophosphate in actual production and life. However, the electronic conductivity of sodium iron phosphate pyrophosphate positive electrode materials is not ideal, the synthesis process requirements are high, the compaction density is low, and inactive impurity phase NaFePO4 is produced during the preparation process, which affects the rate performance and reversible capacity of the material. In response to the above problems, the mainstream elements of the current ion doping modification method are mostly low-valent elements, with the highest being only pentavalent ions. For example: Patent CN116682946A discloses a method for preparing a magnesium and copper co-doped sodium iron phosphate pyrophosphate positive electrode material; Patent CN118630202A discloses a method for preparing a metal niobium doped sodium iron phosphate pyrophosphate positive electrode material. Although these methods can effectively solve the problems of low conductivity and impurity generation, the effects of these modification methods are not comprehensive enough and do not solve the problem of low compaction density of the material, which is insufficient to meet the needs of sodium iron pyrophosphate positive electrode materials. Therefore, a simple and efficient method for synthesizing high-performance sodium iron pyrophosphate positive electrode materials is urgently needed. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a sodium iron pyrophosphate positive electrode material doped with a high-valent transition metal element and iron defects, and to solve the technical problems of poor conductivity, poor ionic conductivity, low compaction density, and easy generation of inactive impurities during the preparation process of the sodium iron pyrophosphate positive electrode material, which affect its electrochemical performance, by doping with a high-valent transition metal element and regulating the iron defect sites.

[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:

[0006] The present invention discloses a high-valent transition metal element doped sodium iron pyrophosphate positive electrode material with iron defects, including the following structure: Na4Fe 3-3x A x (PO4)2(P2O7); wherein the high-valent transition metal element A includes one or more of Mo and W, and x is 0.01-0.5.

[0007] Preferably, Na4Fe 3-3x A x (PO4)2(P2O7) is a pure phase material.

[0008] A method for preparing a high-valent transition metal element-doped sodium iron pyrophosphate positive electrode material with iron defects, the specific steps of which are:

[0009] (1) First, the cathode material source and the carbon source are sequentially added into a ball mill, and after high-energy ball milling, a precursor with a particle size D50 of 200-800 nm is obtained;

[0010] (2) annealing the precursor obtained in step (1) at 450-650° C. for 8-20 h under argon to obtain a sodium iron pyrophosphate positive electrode material doped with a high-valent transition metal element and iron defects.

[0011] In step (1), the positive electrode material source includes a sodium source, an iron source, a phosphorus source, and an A source;

[0012] Wherein, the sodium source includes but is not limited to at least one of sodium carbonate, sodium oxalate, sodium acetate, sodium hydroxide, sodium citrate, sodium sulfate, sodium phosphate, sodium dihydrogen phosphate and sodium pyrophosphate;

[0013] The iron source includes, but is not limited to, at least one of ferrous sulfate, ferrous oxalate, ferrous acetate, ferric phosphate, ferric nitrate, ferrous phosphate, ferrous oxide, and ferrous oxide;

[0014] The A source includes one or more of an A-containing acetate, an A-containing acetate hydrate, an A-containing oxide, and an A-containing ammonium salt;

[0015] The phosphorus source includes, but is not limited to, at least one of monoammonium phosphate, diammonium phosphate, phosphoric acid, triammonium phosphate, and sodium dihydrogen phosphate;

[0016] The carbon source includes, but is not limited to, at least one of sucrose, citric acid, glucose or polyethylene glycol.

[0017] In the above technical solution, the molar ratio of sodium element, iron element, A element and phosphorus element in the sodium source, iron source, A source and phosphorus source is 4:1.5-3:0.01-0.5:4.

[0018] In the above technical solution, the mass ratio of the carbon source to the positive electrode material source is 1:2-17.

[0019] In the above technical solution, the rotation speed of the high-energy ball mill is 500-1000 rpm, and the ball milling time is 5-10 hours.

[0020] The present invention also discloses an application of the above-mentioned high-valent transition metal element-doped sodium iron phosphate pyrophosphate positive electrode material in preparing a positive electrode of a sodium ion battery.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The modified material Na4Fe in the molybdenum (tungsten)-doped sodium ion battery positive electrode material of the present invention 3-3x A x(PO4)2(P2O7) is a fast ion conductor material with stable structure. By replacing the iron sites with molybdenum (tungsten) ions, the surrounding electron cloud density can be reduced without affecting its structural stability, reducing the attraction between unit cells and promoting crystal nucleation. The increase in the number of nuclei makes it impossible for the particles to grow in time, thereby achieving the stacking of a large number of small particles and increasing the compaction density of the material.

[0023] (2) In the present invention, a certain number of iron vacancies are produced under the condition of charge conservation by doping with molybdenum (tungsten) at high potential, which reduces the electrostatic repulsion of sodium ions during the transmission process and can significantly increase the diffusion rate of sodium ions, thereby improving the electrochemical properties of the material.

[0024] (3) The appearance of iron defects in the present invention can create an iron-deficient atmosphere, in which the sodium iron pyrophosphate positive electrode material is more likely to be formed, which can effectively inhibit the formation of the sodium iron phosphate impurity phase and improve the discharge specific capacity and cycle life of the material.

[0025] (4) The present invention is simple to prepare and has low cost. The obtained sodium ion battery positive electrode material has the advantages of high energy density, high specific capacity, high compaction density, etc., which can significantly improve the practicality of the positive electrode material and can be applied to actual production and life.

[0026] In summary, the present invention obtains a sodium iron phosphate pyrophosphate positive electrode material doped with a high-valent transition metal element and with iron defects having good electrochemical properties through simple reactions, high-energy ball milling and high-temperature annealing; the present invention replaces part of the iron sites in the sodium iron phosphate pyrophosphate positive electrode material and creates part of the iron defects by using molybdenum elements, thereby improving the electrochemical properties and compaction density of the sodium iron phosphate pyrophosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD patterns of the products of Comparative Example 1 (a) and Example 6 (b);

[0028] Figure 2 This is the SEM image of the positive electrode material of Example 6;

[0029] Figure 3 This is the first cycle charge and discharge curve of the battery in Example 1;

[0030] Figure 4 The battery rate charge and discharge curve of Example 1;

[0031] Figure 5 This is the first cycle charge and discharge curve of the battery in Example 6;

[0032] Figure 6 This is the battery rate charge and discharge curve of Example 6;

[0033] Figure 7 This is the first cycle charge and discharge curve of the battery of Comparative Example 1;

[0034] Figure 8 This is the battery rate charge and discharge curve of Comparative Example 1. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0036] Example 1

[0037] Preparation of molybdenum-doped and iron-deficient sodium iron phosphate pyrophosphate cathode material: Sodium carbonate is used as a sodium source, ferrous oxalate is used as an iron source, molybdenum trioxide is used as a molybdenum source, ammonium dihydrogen phosphate is used as a phosphorus source, and citric acid is used as a carbon source; the steps are as follows: First, sodium carbonate, ferrous oxalate dihydrate, molybdenum trioxide, ammonium dihydrogen phosphate, and citric acid are added to a ball mill in sequence, and then ball milled at 800 rpm for 8 hours to obtain a precursor with a particle size D50 of 150 nm. The precursor is then annealed at 550°C for 12 hours under nitrogen to obtain a molybdenum-doped sodium iron phosphate pyrophosphate cathode material.

[0038] In this embodiment, the molar ratio of sodium, iron, molybdenum and phosphorus in the sodium source, iron source, molybdenum source and phosphorus source is 4:2.96:0.04:4, that is, the amount of sodium carbonate added to the ball mill is 2 mol, the amount of ferrous oxalate dihydrate added to the ball mill is 2.96 mol, the amount of molybdenum trioxide added to the ball mill is 0.04 mol, the amount of ammonium dihydrogen phosphate added to the ball mill is 4 mol. The amount of citric acid added to the ball mill is 0.4 mol.

[0039] Example 2

[0040] Compared with Example 1, the present embodiment is different in that the molar ratio of sodium element, iron element, molybdenum element and phosphorus element in the sodium source, iron source, molybdenum source and phosphorus source is 4:2.93:0.07:4, the addition amount of ferrous oxalate dihydrate is 2.93 mol, the addition amount of molybdenum trioxide is 0.07 mol, and the other conditions and parameters are the same as those in Example 1.

[0041] Example 3

[0042] Compared with Example 1, the difference between this embodiment and Example 1 is that the molar ratio of sodium element, iron element, molybdenum element and phosphorus element in the sodium source, iron source, molybdenum source and phosphorus source is 4:2.9:0.1:4, the addition amount of ferrous oxalate dihydrate is 2.9 mol, the addition amount of molybdenum trioxide is 0.1 mol, and the other conditions and parameters are the same as those in Example 1.

[0043] Example 4

[0044] Compared with Example 1, the present embodiment is different in that the iron content is reduced to form iron defects, there is no molybdenum source, the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:2.79:4, the addition amount of ferrous oxalate dihydrate is 2.79 mol, no molybdenum trioxide is added, and other conditions and parameters are the same as Example 1.

[0045] Example 5

[0046] Compared with Example 1, the present embodiment is different in that the iron content is reduced to form iron defects, wherein the molar ratio of sodium element, iron element, molybdenum element and phosphorus element in the sodium source, iron source, molybdenum source and phosphorus source is 4:2.88:0.04:4, the addition amount of ferrous oxalate dihydrate is 2.7 mol, and other conditions and parameters are the same as Example 1.

[0047] Example 6

[0048] Compared with Example 5, this embodiment is different in that the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source, molybdenum source and phosphorus source is 4:2.79:0.07:4, the added amount of ferrous oxalate dihydrate is 2.79 mol, and other conditions and parameters are the same as Example 5.

[0049] By comparison Figure 1 It can be seen from the XRD of Comparative Example 1 and Example 6 that there is a peak of impure phase sodium iron phosphate near 33° in Comparative Example 1, while there is no peak in the XRD diagram of Example 6, which proves that the design of molybdenum doping and iron defects can inhibit the formation of impure phases, thereby improving the capacity of the material and the corresponding electrochemical performance.

[0050] from Figure 2 It can be seen that the particles of the material are evenly distributed and have good compaction.

[0051] Example 7

[0052] Compared with Example 5, this embodiment is different in that the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source, molybdenum source and phosphorus source is 4:2.7:0.1:4, the added amount of ferrous oxalate dihydrate is 2.7 mol, and other conditions and parameters are the same as Example 5.

[0053] Comparative Example 1

[0054] This comparative example provides a modified acid sodium iron pyrophosphate positive electrode material and a preparation method thereof. The preparation method is the same as that in Example 1. The difference from Example 1 is that no molybdenum source is added in this comparative example, and the molar ratio of sodium element, iron element and phosphorus element in the sodium source, iron source and phosphorus source is 4:3:4.

[0055] Performance Testing:

[0056] (1) Assembling batteries: The positive electrode materials prepared in the examples and comparative examples were used as positive electrode active materials, and the positive electrode sheets prepared by mixing acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 were used as positive electrodes. A metal sodium sheet was used as a counter electrode. 5 Vol% fluoroethylene carbonate was added to a 1 M NaClO4 / propylene carbonate solution as an electrolyte. Glass fiber was used as a separator. Button batteries were assembled in a glove box with a high-purity argon atmosphere.

[0057] (2) Test method: The electrochemical performance of button cells was tested in a voltage window of 1.7-4.3V.

[0058] The results are shown in Table 1 and Figure 2-7 As shown. Among them, Figure 3 The first charge-discharge curve of the button cell assembled with the molybdenum-doped sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 of the present invention at a cycle rate of 0.1C is shown in FIG. Figure 4 This is a rate performance diagram of a button cell assembled with a molybdenum-doped sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 of the present invention. Figure 5 The first charge-discharge curve of the button cell assembled with the molybdenum-doped and iron-deficient sodium iron phosphate pyrophosphate positive electrode material prepared in Example 6 of the present invention at a cycle rate of 0.1C is as follows: Figure 6 This is a rate performance diagram of a button cell assembled with a molybdenum-doped and iron-deficient sodium iron pyrophosphate positive electrode material prepared in Example 6 of the present invention. Figure 7 The first charge-discharge curve of the button cell assembled with the pure phase sodium iron phosphate pyrophosphate positive electrode material prepared in Comparative Example 1 of the present invention at a cycle rate of 0.1C is shown in FIG. Figure 8 This is a rate performance diagram of a button cell assembled with the sodium iron phosphate pyrophosphate positive electrode material prepared in Comparative Example 1 of the present invention.

[0059] Table 1 Performance indicators of various materials in the case

[0060]

[0061] It can be seen from the above test results that the composite phosphate-based positive electrode material prepared in the embodiment of the present application can better improve the compaction density and gram capacity of the sodium iron phosphate pyrophosphate positive electrode material. In addition, by doping the iron site with molybdenum (tungsten) elements, the electrochemical properties such as capacity and cycle stability of the sodium iron phosphate pyrophosphate positive electrode material can be further improved. Therefore, the compaction density of the sodium iron phosphate pyrophosphate positive electrode material in the embodiment of the present application is not less than 1.9g / cm 3 The applied battery showed better 0.1C charge and discharge performance and rate performance.

[0062] By comparing Examples 1 to 3, it can be seen that when the amount of molybdenum source added in Example 1 is 0.07 mol, the sodium iron pyrophosphate positive electrode material exhibits better 0.1C and 1C rate charge and discharge performance after being applied to the battery. The substitution of molybdenum for iron can improve the compaction density and electrochemical performance of the sodium iron pyrophosphate positive electrode material.

[0063] By comparing Example 1 with Examples 5 to 7, it can be seen that when the amount of molybdenum source added in Example 6 is 0.07 mol and the amount of iron defects is 0.21 mol, the sodium iron phosphate pyrophosphate positive electrode material shows better 0.1C and 1C rate charge and discharge performance after being applied to the battery. The substitution of iron by molybdenum and iron defects can improve the compaction density and electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material. Iron defects can inhibit the formation of heterogeneous sodium iron phosphate, thereby improving the electrochemical performance of the material.

[0064] However, the sodium iron pyrophosphate positive electrode material in Comparative Example 1 is only coated with carbon material, which reduces the electrochemical performance and compaction density of the sodium iron pyrophosphate positive electrode material.

Claims

1. A high-performance sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The structural formula is: Na4Fe 3-3x A x (PO4)2(P2O7); wherein the high-valent transition metal element A includes one or more of Mo and W, and x is 0.01-0.

5.

2. The high-performance sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: Na4Fe 3-3x A x (PO4)2(P2O7) is a pure phase material.

3. The method for preparing a high-performance sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The specific steps are: (1) First, a cathode material source and a carbon source are sequentially added to a ball mill, and after high-energy ball milling, a precursor with a particle size D50 of 200-800 nm is obtained; the cathode material source comprises a sodium source, an iron source, a phosphorus source, and an A source; A comprises one or more of Mo and W; (2) annealing the precursor obtained in step (1) at 450-650° C. for 8-20 h under argon to obtain a sodium iron pyrophosphate positive electrode material doped with a high-valent transition metal element and iron defects.

4. The preparation method according to claim 3, characterized in that: In step (1), The sodium source includes, but is not limited to, at least one of sodium carbonate, sodium oxalate, sodium acetate, sodium hydroxide, sodium citrate, sodium sulfate, sodium phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate; The iron source includes, but is not limited to, at least one of ferrous sulfate, ferrous oxalate, ferrous acetate, ferric phosphate, ferric nitrate, ferrous phosphate, ferrous oxide, and ferrosoferric oxide; The A source includes one or more of an A-containing acetate, an A-containing acetate hydrate, an A-containing oxide, and an A-containing ammonium salt; The phosphorus source includes, but is not limited to, at least one of monoammonium phosphate, diammonium phosphate, phosphoric acid, triammonium phosphate, and sodium dihydrogen phosphate; The carbon source includes, but is not limited to, at least one of sucrose, citric acid, glucose or polyethylene glycol.

5. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of sodium element, iron element, A element and phosphorus element in the sodium source, iron source, A source and phosphorus source is 4:1.5-3:0.01-0.5:

4.

6. The preparation method according to claim 3, characterized in that: In step (1), the mass ratio of the carbon source to the positive electrode material source is 1:2-17.

7. The preparation method according to claim 3, characterized in that: In step (1), the rotation speed of the high energy ball mill is 500-1000 rpm, and the ball milling time is 5-10 h.

Citation Information

Patent Citations

  • Doped modified ferric sodium pyrophosphate positive electrode material and preparation method thereof

    CN116682946A

  • Preparation method of metal niobium doped ferric sodium pyrophosphate positive electrode material and vehicle

    CN118630202A

Cited By

  • High-compaction ferric sodium pyrophosphate positive electrode material and preparation method thereof

    CN120348921A

  • Composite phosphate positive electrode material of sodium ion battery and preparation method of composite phosphate positive electrode material

    CN121097070A